Vertical Distribution of Ectomycorridzae in Deodar and Chir Pine Forests in Relation to their Soil Characteristics - Rawat, P. S.; Ginwal, H. S.; Singh, R. P.; Dubey, R. C. (Indian Forester, 2003)
Vertical distribution of ectomycorrhizae in natural forests of Deodar (Cedrus deodara) and Chir pine (Pinus roxburghii) of Central Himalayas has been studied in relation to soil properties at various soil depths (0-30 cm). Soil moisture, pH, organic C. organic matter, total N and available P decreased along the soil depths in both of forest. Live, dead and total mycorrhizal counts were more in C. deodara and P. roxburghii. Highest numbers ofmycorrhizae were recorded between 6-10 cm depth. Apparently, a drastic change in mycorrhizae counts were recorded at soil depth below 15 cm significantly, (P<O.O1) a negative correlation was founa between soil depth and mycorrhizal counts (live and dead) and that of positive correlation between live and dead ones. Moreover, a positive correlation between mycorrhizal counts and organic matter, total N available P was estimated.